Qualidade físico-química e sensorial das alfaces das cultivares Romanela e Rubinela produzidas em diferentes sistemas de cultivo - Rossi, Cláudia Margareth Abe (2017)
Lettuce is one of the vegetables with the highest consumption and economic importance worldwide, extensively cultivated in all continents, particularly in temperate and subtropical regions. In Brazil, there is a market that explores new varieties for the tropical climate. The cultivars Romanela and Rubinela are innovative varieties, since they are crunchy and tropicalized. Lettuce cultivation can be carried out in different cropping systems, which have different characteristics in their management practices and can influence the quality parameters of this vegetable. The aim of this work was to verify the physical, physicochemical and sensory quality of these cultivars produced in conventional, hydroponic and organic systems. The plantings of the conventional system and the hydroponic system were conducted in the experimental area of CCA – UFSCar; the organic system was performed in a ranch in the city Cordeirópolis - São Paulo State. After the harvest, the samples were evaluated regarding leaf area, leaf size, unit leaf area, fresh mass, mass loss, turgidity pressure, instrumental color, pH, total soluble solids (TSS), total titrable acidity (TTA), total phenolic compounds (TPC), and sensory characterization. The cultivation systems influenced the physical characteristics size, weight and mass loss of the Romanela lettuce. For the Rubinela lettuce, the type of cultivation influenced in fresh mass and mass loss. The organic cultivar (cv) Romanela presented dark green color and superior values for pH, TSS and TPC. The hydroponic Romanela had the highest value for TTA. The organic cv. Rubinela presented the most intense red color and the highest STT and TPC values. The hydroponic Rubinela lettuce presented the lowest pH and TPC values and the highest TTA value. In the sensory analysis, the evaluators noticed a difference in the attributes green color, leaf size and crunchiness, grassy aroma and sweet taste for the Romanela cv. The conventional and hydroponic Romanela lettuce presented the highest preference. For cv. Rubinela, the evaluators noticed a difference in the attributes purple and green colors, leaf thickness and size, sweet and bitter tastes. The conventional and hydroponic Rubinela lettuce were the preferred, with the hydroponic presenting the highest purchase intention. Therefore, the physical-chemical and sensorial characteristics of the new lettuce, Romanela and Rubinela cultivars were influenced by the conventional, hydroponic and organic cultivation system, generating production and post-harvest information of importance for the producer and consumer.